PENENTUAN TITIK LOKASI DAN DESAIN LAYOUT TERMINAL ANGKUTAN BARANG KABUPATEN BLITAR (FSTPT Indonesia, 2023)
Blitar Regency is an area that is especially strategic for freight transportation because it is located on a crossing route that connects areas in the southern region of East Java Province. Blitar Regency has a superior production sub-sector, namely the result where the commodity is chicken eggs. It is proper that the pattern of movement of goods transport in Blitar Regency is supported by facilities and infrastructure to support the movement of the flow of goods transport traffic, one of which is the Goods Transport Terminal. In Blitar Regency there is no Goods Transportation Terminal, this can hamper the distribution of goods, therefore it is necessary to determine the location of the goods terminal in Blitar Regency .It is necessary to hold direct observations or several surveys conducted in the field to determine the point of transportation of the goods. The determination of the location of the goods transportation point leads to the policy of the Regional Spatial Planning (RTRW) of Blitar Regency because there are several proposals from the government and also a proposal for a technical approach. In the research to determine the location of the construction of the Freight Transport Terminal using the Composite Performance Index (CPI) decision-making method which includes analysis of accessibility criteria, analysis of traffic performance criteria, analysis of environmental sustainability and analysis of initial investment costs. By considering the direction of policy and development as well as the suitability of the Blitar Regency Spatial Plan. ABSTRAK Kabupaten Blitar merupakan daerah yang strategis terutama untuk perlintasan angkutan barang karena berada di jalur perlintasan yang menghubungkan daerah di wilayah selatan Provinsi Jawa Timur. Kabupaten Blitar terdapat produksi subsektor yang diunggulkan yaitu hasil peternakan di mana komoditas ayam ras petelur. Sudah selayaknya pola pergerakan angkutan barang di Kabupaten Blitar didukung sarana dan prasarana untuk menunjang pergerakan arus gerak lalu lintas angkutan barang salah satunya Terminal Angkutan Barang. Di Kabupaten Blitar belum ada Terminal Angkutan Barang, hal ini dapat menghambat distribusi barang, oleh karena itu perlu diadakannya penentuan titik lokasi terminal barang di Kabupaten Blitar. Perlu diadakannya observasi secara langsung atau beberapa survey yang dilakukan di lapangan untuk menentukan titik angkutan barang tersebut. Penentuan titik lokasi angkutan barang mengarah pada kebijakan Rancangan Tata Ruang Wilayah (RTRW) Kabupaten Blitar dikarenakan ada beberapa usulan dari pemerintah dan juga usulan pendekatan teknis. Dalam penelitian penentuan titik lokasi pembangunan Terminal Angkutan Barang dengan menggunakan metode pengambil keputusan Composite Performance Indeks (CPI) yang meliputi analisis kriteria aksesibilitas, analisis kriteria kinerja lalu lintas, analisis kelestarian lingkungan serta analisis biaya investasi awal. Dengan mempertimbangkan arah kebijakan dan pengembangan serta kesesuaian Rencana Tata Ruang Wilayah Kabupaten Blitar.